Laboratory Evaluation of Neem formulation bioactivity against Crocidolomia pavonana F. larvae - Ramadhan, Raden Arif Malik; Widayani, Neneng Sri; Dono, Danar (CROPSAVER - Journal of Plant Protection, 2018)
This study aims to evaluate the bioactivity of the Neem formulationÂ  against Crocidolomia pavonana larvae in the laboratory. The study using six treatments and three replications. The treatment consisted of control, the neem formulaconcentrations of 0.3%, 0.5%, 0.8%, 1.3%, and 2.3%. The test was done by leaf feeding method and tested on C. pavonana instar II. The results showed that the neem formulation 2.3% could increase mortality of C. pavonana larvae with mortalityrate of 95% population and LCÂ  value aqual to 0.82973. Neem formulation can inhibit the development of C. pavonanalarvae from instar I to instar IV, decrease feed intake, and decrease the dry weight of C. pavonana larvae instar IV. Keywords: Azadirachta indica, Bioactivity, Crocidolomia pavonana, neem formulation